ANALISIS PENDAPATAN USAHATANI PADI DI DESA SUNGAI KINJIL KECAMATAN BENUA KAYONG KABUPATEN KETAPANG - POPIDYLAH, POPIDYLAH; RADIAN, RADIAN; SUYATNO, ADI (Jurnal Social Economic of Agriculture, 2015)
The purpose of research is to analyze farm revenue with and without rice threshing tool, the level of efficiency of the use of power thresher with traditional types of rice farmers in Sungai Kinjil Benua Kayong District of Ketapang. The research method used was a survey method. Locations were selected intentionally (purposive) Sungai Kinjil Village, Sub Benua Kayong Ketapang Farmers considering that the village has much to apply the use of Power Thresher to help process threshing grain at harvest, but there are still many farmers who still use traditional tools gebuk or slam. The research is result the cost of the rice farmers of using the power thresher up forms of grain is Rp. 13,853,939 per hectare, up form of rice is Rp. 16,718,182, per hectare. Cost of the rice farmers using traditional tools up forms of grain is Rp. 13,929,721 per hectare, up form of rice is Rp. 16,706,691, per hectare. The revenue of the rice farmers of using the power thresher up forms of grain is Rp. 22,909,090 per hectare, up form of rice is Rp. 24,434,378, per hectare. Cost of the rice farmers using traditional tools up forms of grain is Rp. 19,636,363 per hectare, up form of rice is Rp. 21,901,964, per hectare. Analysis of the balance R/C ratio for farmers using the power Thresher from grain sales is: 1.65 while the balance Analysis Ratio R/C for Farmers from rice sales is: 1.46. Analysis of the balance of R/C for farmers not using the power thresher from grain sales is: 1.41 while the balance Analysis of R/C ratio for farmers from rice Sales is: 1.31. From the results of different test (t-test) showed no difference between the revenue of farmers who use power thresher with farmers who do not use the power thresher both regional sales revenue of rice and rice sales significantly by 95% confidence level